Ubiquitin and the Brain: Roles of Proteolysis in the Normal and Abnormal Nervous System - Ashok N. Hegde (Frontiers Research Topics, 2017)
Proteolysis by the ubiquitin-proteasome pathway (UPP) in the nervous system has been extensively studied both in the context of normal physiological function as well as abnormal pathological conditions. Although ubiquitin was used as a marker of brain pathology, the normal functions of the UPP were not studied much in the nervous system until the 1990s. The early investigations focused on synaptic plasticity which was followed by studies on the roles of protein degradation in the development of the nervous system. Research on the role of abnormal roles of the UPP follows a parallel trajectory. Since the 2000s, the field has grown to encompass many subareas of research and several model systems. Despite the progress made, many unanswered questions still remain. For example, there are many unknowns about the precise spatial and temporal control of protein degradation in the normal nervous system. With respect to the roles of proteolysis in brain pathology a major challenge is to elucidate the connection between impaired protein degradation and disease progression. In addition, in-depth studies of the roles of ubiquitin-proteasome-mediated proteolysis in neurodegenerative diseases are promising in identifying therapeutic targets. This ebook contains original research papers and insightful reviews that cover several aspects of proteolysis by the UPP and its physiological as well as pathological functions in the nervous system.